Oxidative Electrocyclization of Diradicaloids: C-C Bonds for Free or How to Use Biradical Character for π-Extension - Feofanov, Mikhail; Akhmetov, Vladimir; Sharapa, Dmitry I.; Amsharov, Konstantin (Organic Letters, 2020)
Herein, we show that biradical character and appropriate distribution of spin density can be used for synthetic purposes. We demonstrate the rational domino annulation that includes dehydrative π-extension (DPEX) as the initiation step and subsequent oxidative electrocyclizations (EC) promoted by favorable localization of the unpaired electrons enabling up to four C-C bonds formed during the reaction. Contradicting to the Woodward-Hoffmann rules, the reaction proceeds at room temperature, whereas termination occurs when biradical character vanishes.
CRIS-Team Scopus Importer:2020-07-10